Increased biological antioxidant potential in the cerebrospinal fluid of transient global amnesia patients - Takayuki Kawai (Nature Portfolio, 2021)
Abstract Oxidative stress may accompany the pathological process in transient global amnesia (TGA). We measured the biological antioxidant potential (BAP) in the cerebrospinal fluid (CSF) of TGA patients. We enrolled 13 TGA patients (7 men, 6 women; mean age 65.0 years [48–70 years]) and 24 control subjects (12 men, 12 women; mean age 38.2 years [17–65 years]; age did not correlate with csfBAP in this group). We performed brain MRI in all TGA patients, and CA1 lesions were noted by MRI in 5 subjects. We measured csfBAP, total antioxidant properties, in all TGA patients and controls. csfBAP levels were higher in TGA patients than in controls (p = 0.024, 0.028). csfBAP levels in TGA patients did not differ between MRI-positive and -negative subgroups. Elevated csfBAP levels were observed in TGA patients, suggesting that oxidative stress may have a role in the pathogenesis of TGA.